Improving inpatient care for older adults: Implementing Dementia Commissioning for Quality and Innovation (CQUIN) - Harrison, Judith R (BMJ Qual Improv Rep, 2017)
Dementia is a common condition, and people with dementia occupy around 25% of hospital beds. Commissioning for Quality and Innovation (CQUIN) is an NHS payment framework that links part of English healthcare providers' income to quality improvement. The dementia CQUIN goals are designed to encourage the recognition of dementia in hospital. The Royal Surrey County Hospital, Guildford, introduced new procedures to meet the dementia CQUIN targets. Adherence to the changes was a problem. This project aimed to improve hospital's implementation strategy. At baseline, completion rates for dementia CQUIN assessments were just 27%. Interventions were informed by semi-structured interviews with junior doctors and dementia leads in neighbouring trusts. Progress was measured by regular audits and interventions were made over several months. Changes suggested by junior doctors and nurses proved very effective, and involving the multidisciplinary team produced the most significant improvement. Gradual progress was made until we achieved and maintained 90% completion for dementia assessments. In conclusion, we made changes to working practices to achieve the CQUIN targets and promoted quality care for older adults. Our experience highlighted the importance of involving multidisciplinary frontline staff in the design of service changes.